Integrated sediment quality assessment in Paranagua Estuarine System, Southern Brazil - Choueri, R. B.; Cesar, A.; Torres, R. J.; Abessa, Denis Moledo de Souza [UNESP]; Morais, R. D.; Pereira, C. D. S.; Nascimento, M. R. L.; Mozeto, A. A.; Riba, I.; DelValls, T. A. (Academic Press Inc. Elsevier B.V., 2009)
Sediment quality from Paranagua Estuarine System (PES), a highly important port and ecological zone, was evaluated by assessing three lines of evidence: (1) sediment physical-chemical characteristics; (2) sediment toxicity (elutriates, sediment-water interface, and whole sediment); and (3) benthic community structure. Results revealed a gradient of increasing degradation of sediments (i.e. higher concentrations of trace metals, higher toxicity, and impoverishment of benthic community structure) towards inner PES. Data integration by principal component analysis (PCA) showed positive correlation between some contaminants (mainly As, Cr, Ni, and Pb) and toxicity in samples collected from stations located in upper estuary and one station placed away from contamination sources. Benthic community structure seems to be affected by both pollution and natural fine characteristics of the sediments, which reinforces the importance of a weight-of-evidence approach to evaluate sediments of PES. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Weight-of-evidence approach; Multivariate analysis; Sediment toxicity; Sediment contamination; Macrobenthic community